Comprehensive study on solar air heater with circular and V-type turbulators attached on absorber plate. (August 2015) - Rajaseenivasan, T.; Srinivasan, S.; Srithar, K.
Abstract: Performance enrichment in a single pass SAH (solar air heater) with circular and V-shape inserts are considered in this paper. Two identical SAH: conventional and modified SAH are tested with different Reynolds number ranging from 6000 to 12, 000. Circular and V-shape turbulators are fixed in the absorber plate of modified SAH at six different configurations; inline arrangements with 4 × 4 (type-a), 5 × 4 (type-b), 6 × 4 (type-c) and 6 × 4 zigzag arrangement of circular inserts (type-d). Experiments are extended by introducing V-type inserts in convex (type-e) and concave shape (type-f) to create additional turbulence motion. Experiment results revealed that the system efficiency increases with Reynolds number and number of turbulators in absorber plate. Air temperature reaches an upper value of 66 °C in type-f with the mass flow rate of 57.7 kg/hr. Nusselt number increases with the Reynolds number and reaches the maximum of 210 for type-f turbulators at Reynolds number of 11615. Thermal enhancement factor decreases with increase in Reynolds number for all modifications. First law, thermohydraulic and second law efficiency increases up to 85%, 63% and 45% respectively for type-f at Reynolds number of 11615. Theoretical analysis also carried out and agrees well with experimental results. Graphical abstract: Highlights: Two single pass solar air heaters are fabricated and experimentally evaluated. Circular and V-type turbulators are used in six different configurations. Maximum air temperature of 66 °C is achieved. SAH performance is improved with mass flow rate and turbulators.